Harmonization of the Czech Accounting within the EU Countries - Psenkova, Yvetta (Harmonizacja księgowości w Czechach z krajami Unii Europejskiej, 2008)
The article presents problem of harmonization of the Czech accounting within the EU countries. The author described international accounting standards and stages of the Czech accounting harmonization since 1992. Development of the Czech accountancy has not been finished yet. Accounting has to react to the development of the national as well multinational economic environment and has to reflect the incentives coming from the new world tendencies. (MP)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 278-281